Molecular Simulation on Competitive Adsorption Differences of Gas with Different Pore Sizes in Coal - Han, Qing; Deng, Cunbao; Gao, Tao; Jin, Zhixin (Molecules (Basel, Switzerland), 2022)
Micropores are the primary sites for methane occurrence in coal. Studying the regularity of methane occurrence in micropores is significant for targeted displacement and other yield-increasing measures in the future. This study used simplified graphene sheets as pore walls to construct coal-structural models with pore sizes of 1 nm, 2 nm, and 4 nm. Based on the Grand Canonical Monte Carlo (GCMC) and molecular dynamics theory, we simulated the adsorption characteristics of methane in pores of different sizes. The results showed that the adsorption capacity was positively correlated with the pore size for pure gas adsorption. The adsorption capacity increased with pressure and pore size for competitive adsorption of binary mixtures in pores. As the average isosteric heat decreased, the interaction between the gas and the pore wall weakened, and the desorption amount of CH4 decreased. In ultramicropores, the high concentration of CO2 (50–70%) is more conducive to CH4 desorption; however, when the CO2 concentration is greater than 70%, the corresponding CH4 adsorption amount is meager, and the selected adsorption coefficient SCO2/CH4 is small. Therefore, to achieve effective desorption of methane in coal micropores, relatively low pressure (4–6 MPa) and a relatively low CO2 concentration (50–70%) should be selected in the process of increasing methane production by CO2 injection in later stages. These research results provide theoretical support for gas injection to promote CH4 desorption in coal pores and to increase yield.